Threefold relationship between ideal humanity and sublime beauty in Chinese art forms - Ding, Maoyuan; Tan, Xiao (Frontiers in Psychology, 2025)
In Chinese thought, the concept of the “sublime” is closely intertwined with “beauty,” the two concepts merging to form a sublime beauty that seeks the continuous development of universal life amid change. This paper explores the multifaceted relationship between the Chinese artistic mind and sublime beauty through three dimensions of the research model: potential, processes, and goals. In terms of potential, Chinese artistic thought places full trust in the inherent potential of an individual’s ideal humanity, emphasizes the awakening of the sublime beauty within each person through specific art forms, and cultivates different perspectives to understand the connection between the mind and the sublime beauty of our world. In terms of process, Chinese artistic thought is characterized by the focused sincerity of the creative mindset; creative thinking that balances the “degree” of rational expression of emotions and the “qi” cultivated through daily spiritual practice; and the cognition of the sublime, which combines the gradual enlightenment gained from daily experiences of embodied cognition with the sudden enlightenment triggered by creative talent. In terms of artistic goals, ideal humanity in pursuit of sublime beauty is divided into three states: the “self state” that manifests the style of the individual subject, the “no-self state” that transcends the limitations of the self, and the “empty state” that surpasses even the cognitive notion of “transcending the self.” The threefold relationship between ideal humanity and sublime beauty in Chinese art can provide contemporary psychology with research model and unique perspectives on being aware of one’s self-potential, understanding their emotions and other aspects of the mind, and constructing multiple value goals.